1999
DOI: 10.1007/s100510050749
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-mediated interactions of fluid membranes in a lyotropic lamellar phase: a small angle X-ray and neutron scattering study

Abstract: Small angle X-ray and neutron scattering data on an effective three-component lamellar phase composed of water, a non adsorbing water-soluble polymer (polyvynilpyrolidone), fluid membranes, made from a mixture of a cationic surfactant (cetylpiridiumchloride) and a cosurfactant (hexanol), are presented for various membrane as well as polymer concentrations. The data are fitted with a recently proposed model which takes into account the geometry and the fluctuations of these periodic structures. This allows a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
4
40
0
1
Order By: Relevance
“…Recently, several experimental studies have shown that electrostatically stabilized lamellar phases are able to incorporate a large amount of water-soluble neutral polymers [1][2][3]. The properties of these polymer-doped lamellar phases begin to be investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, several experimental studies have shown that electrostatically stabilized lamellar phases are able to incorporate a large amount of water-soluble neutral polymers [1][2][3]. The properties of these polymer-doped lamellar phases begin to be investigated.…”
Section: Introductionmentioning
confidence: 98%
“…From an application point of view, lamellar phases of lipid bilayers have been used, for example, to measure the effect of additives, such as proteins or polymers, on the interaction between membranes [13][14][15]; the interpretation of these results depends strongly on the distance dependence of the fluctuation pressure. Therefore, a profound understanding of lamellar membrane stacks is very important both from a theoretical and an experimental point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Negative contribution of the polymer on the compression modulus B has been reported both for the theoretically and experimentally. 15,16) Lamellar phase is generally stabilized with constant layer distance due to inter-membrane repulsive force. 17) In the presence of the polymer chain dissolved in the water layer, however, the constant layer distance is disturbed in this study, is increased, hydrophobic chain is compressed in the bilayer, and membrane thickness will be inhomogeneous due to the configuration entropy of polymer chain.…”
Section: Rheo-salsmentioning
confidence: 99%